The Influence of hand paddles on the arm coordination in female front crawl swimmers - Gourgoulis, V.; Aggeloussis, N.; Kasimatis, P.; Vezos, N.; Antoniou, P.; Mavromatis, G. (The Journal of Strength and Conditioning Research, 2009)
The purpose of the research was to determine the influence of hand paddles on the arm coordination in female front crawl swimmers. Ten female swimmers swam at a maximal intensity 25 m without, with small hand paddles (116 cm2), and with large hand paddles (286 cm2). Four S-VHS cameras were used to record the underwater motion of both arms, and the digitizing of selected points onto the subject's body was undertaken using the Ariel Performance Analysis System. The mean swimming velocity, the stroke length, the stroke rate, the relative duration of the separate phases of the stroke, and the index of coordination were then calculated. The index of coordination was defined as the time interval between the propulsive phases of the 2 arms expressed as a percentage of the mean duration of the stroke cycle. The results showed that when the hand paddles were worn, the mean swimming velocity (p < 0.05) and the stroke length (p < 0.05) were significantly increased, whereas the stroke rate was significantly decreased (p < 0.05). When large paddles were worn, the relative duration of the whole propulsive phase was significantly decreased (p < 0.05), and the relative duration of the nonpropulsive phase was significantly increased (p < 0.05). However, the index of coordination was remained unchanged under the 3 measurement conditions (p = 0.895). It was concluded that in front crawl hand-paddled swimming, significant increases of the swimming velocity was not caused by modifications in the pattern of arm coordination. Thus, hand-paddled swimming should not be used as a tool to alter the time sequence of the application of propulsive forces generated from the 2 arms.